An interactive E-quiz English learning for preschool children in rural areas / Anis Roslan - Roslan, Anis (2022)
E-Quiz Systems is a system that take the place of manual methods, which are paperless traditional ways that have been employed in rural preschools. This research is an interactive web-based system that will help children and teachers in learning and teaching of English language in rural areas. This research aims to inspire preschool children in rural areas to learn English language while also allowing teachers to assess their children knowledge levels through interactive web-based systems. Using the interactive multimedia principles which are diverse media and navigation with interaction, a web-based application system is designed as a medium to show e-quiz questions. An E-Quiz System is developed as the interactive quiz English learning using interactive multimedia principles. In addition, this project was tested through functionality and usability testing. The methodology used on this project was ADDIE Model. From the findings it has been discovered that this project can gain interest children in learning English and ease the teacher to monitor the progress of children with the score that has been put into the E-Quiz System.